Assessing the Impact of Polymers on the pH‐Induced Precipitation Behavior of Poorly Water Soluble Compounds using Synchrotron Wide Angle X‐Ray Scattering. Issue 9 (6th February 2014) - Hsieh, Yi‐Ling; Box, Karl; Taylor, Lynne S.
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the pH‐induced precipitation behavior of four ionizable compounds (papaverine, dipyridamole, glyburide, and warfarin) in the absence and presence of polymers. Polymers selected included nonionic, anionic, and cationic polymers. Precipitates were analyzed immediately after formation using high‐energy radiation wide‐angle X‐ray scattering analysis and polarized light microscopy. Papaverine immediately crystallized to the original solid‐state form upon creation of a highly supersaturated solution and polymers were unable to prevent crystallization. Dipyridamole also crystallized rapidly, forming a metastable polymorph that was stabilized by several of the cellulosic polymers. For glyburide and warfarin, although the compounds readily crystallized in the absence of the polymers, several of the polymers were able to prevent crystallization for more than 6 h. In general, measurements of solution concentration immediately following precipitation corroborated the solid‐state analysis results, with the solution phase for the noncrystalline precipitates having a concentration considerably higher than that of the equilibrium solubility value, whereas for the crystalline precipitates, values were closer to the equilibrium solubility. Thus, precipitation to a noncrystalline solid was found to be promoted by the presence of some polymers, resulting in the formation of a supersaturated solution. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2724–2735, 2014